Icelandic Deaf Culture: A Discourse Analysis - Haukur Darri Hauksson 1992- (2018)
Icelandic sign language is equal to Icelandic by law, but Icelandic sign language is an endangered language facing a trajectory towards extinction if no changes occur to prevent that from happening. Discourse surrounding deafness in Iceland is based on diverging modules of deafness where governmental and societal institutions discuss hearing loss in terms of pathology on one hand, and in terms of being a cultural and linguistic minority on another. Discourse arising from the governmental institutions The Communication Centre for the Deaf and Hard of Hearing and The National Hearing and Speech Institute of Iceland as well as discourse from the social institutions The Association of the Deaf and The Association of the Hard of Hearing, along with some examples taken from Icelandic media and society, have been analysed with Foucauldian discursive methods to reveal how deafness and Icelandic Sign Language is sometimes contradictorily spoken about at an institutional level. The conclusions of the analysis uncover a wide-spread societal ignorance about the role and function of Icelandic Sign Language in the lives of deaf people and more-so what it fundamentally means to be deaf; in which members of the Deaf community are continuously pushing for recognition as belonging to a cultural and linguistic minority. Íslenskt táknmál er jafnrétthátt íslensku samkvæmt lögum en íslenskt táknmál er í útrýmingarhættu og mun hverfa ef ekkert verður gert til að komast í veg fyrir það. Orðræður sem snúa að heyrnarleysi á Íslandi byggja á ólíkum hugmyndum. Ríkis- og samfélagsstýrðar stofnarnir ræða heyrnarleysi með afar ólíkum hætti en annars vegar er rætt um heyrnarleysi í læknisfræðilegum skilningi og hins vegar er talað um það sem hluti af mál- og menningarminnihlutahóps. Orðræðuvenjur ríkisstofnanna Samskiptamiðstöðvar heyrnarlausra og heyrnarskertra og Heyrnar- og talmeinastöðvar Íslands og samfélagsstofnanna Félag heyrnarlausra og Heyrnarhjálpar, ásamt dæmum úr íslenskum fjölmiðlum og samfélagi, eru teknar fyrir og greindar með ...